Implication of work environment, market and learning orientations on innovation in Indonesia - Yusri Abdillah, Nurminingsih, Umar Nimran, Suharyono, (Opción, 2020)
This study aims to reveal the effect of the work environment, market orientation, learning orientation on innovation, the influence of the work environment on market orientation and learning, and the influence of market orientation on learning orientation in Indonesia. It is utilizing 112 purposive sampling and employing Generalized Structured Component Analysis (GSCA) to analyze data. The results showed that the work environment had a significant positive effect on market orientation, the work environment had a significant positive effect on learning orientation, market orientation had a significant positive effect on learning.